Ashwagandha, Withania somnifera (L.) Dunal, for the prophylaxis against SARS-CoV-2 infection: A multicentric randomized hydroxychloroquine controlled clinical trial in Indian health care workers - Renuka Kulkarni-Munshi; Deepti Talmohite; Anand More; Jaya Chakravarty; Sandhya Kamat; Akash Khobragade; D. Himanshu Reddy; Manish Patel; Divya Kajaria; Raju Singh; Sarita Kumari; Priyanka Mishra; et al. (Journal of Ayurveda and Integrative Medicine, 2025)
Background: The study was planned when, the hydroxychloroquine (HCQ) was the only prophylactic agent approved by health authorities in several countries and no prophylactic COVID-19 vaccine was available. Objective: The present study aimed to evaluate efficacy of Withania Somnifera (L.) Dunal (WS) as a chemoprophylactic and immunomodulatory agent against SARS-CoV-2 infection. Methods: In a 12 week, randomized, open label, parallel group, two arm, comparative, multicentric, controlled trial compared WS with hydroxychloroquine (HCQ) in health care workers (HCWs). Total 400 HCWs were randomized in 1:1 ratio to receive either oral WS (500 mg for 12 weeks) or HCQ 400 mg (for 7 weeks). The primary outcome was to establish equivalence between WS and HCQ for the proportion of participants contracting SARS-CoV-2 infection. Results: Seven participants contracted SARS-CoV-2 infection: 5 in WS arm and 2 in HCQ arm. The equivalence between WS and HCQ was established for the proportion difference of participants contracting SARS-CoV-2 infection for per-protocol (PP) (1.6%, 95% CI: −1.08%–4.33%) and in subgroup analysis (ITT, mIIT, non-vaccinated and seronegative).Notably, the immunomodulatory effect of WS stood scientifically validated by the statistically significant difference in cytokine levels (p < 0.0001) at 12 weeks compared to baseline for Tumor Necrosis Factor (TNF)-alpha, Interleukin (IL)-2, IL-10, IL-17 and Monocyte chemoattractant protein-1 (MCP-1).Gastrointestinal-related AEs were most frequent (53 in WS and 58 in HCQ). Headache and sneezing were observed only with HCQ. Participant global assessment showed excellent tolerability with both treatment arms. Conclusion: WS was found equivalent to HCQ as a prophylactic against SARS-CoV-2 infection with no safety concern. WS is thus inferred to be an effective and safe Ayurvedic intervention for prophylaxis against SARS-CoV-2 infection, and also as an immunobooster.